Creative tourism as a dynamizer of local economies: A case study in an Afro-descendant community - Betancur-Rodríguez, Víctor H. (2022)
Creative tourism is currently emerging as a differential and alternative proposal for experiences to vindicate the cultural, environmental and artistic aspects, while the tourist simulates immersive interaction with social, cultural and natural landscapes. This article develops a case study with the village community of La Puerta, San Nicolás de quebrada seca, municipality of Sopetrán, Antioquia, in order to analyze the possibilities of tourism use, which can be accessed by the inhabitants of the Afro-descendant collective territory of the village of La Puerta, in Sopetrán, Antioquia, from the approach of the orange economy. For this purpose, a qualitative research method was applied, from a participatory and interactive methodological approach, with the predominance of techniques such as sociographic analysis and group discussion. Recognition of the modes of representation and territorial action of the community of La Puerta, in terms of the dynamization of social and community processes, which advocate for the protection of the ecosystemic patrimony, La Bramadora wetland. 2. Description of the process of insertion of a sustainable, creative and vindicating tourism, through conservation practices, such as bird watching, that stimulate and dynamize the development of the local economy. It is concluded that orange tourism is a dynamizer of local economic development par excellence, besides being one of the clearest bets in the process of economic recovery of the tourism sector in general.